Effect of 9-β-d-Arabinofuranosyladenine 5′-Monophosphate and 9-β-d-Arabinofuranosylhypoxanthine 5′-Monophosphate on Experimental Herpes Simplex Keratitis - Kaufman, Herbert E. (1976)
Treatment of established experimental keratitis caused by herpes simplex virus with 9-β-d-arabinofuranosyladenine 5′-monophosphate (Ara-AMP) or 9-β-d-arabinofuranosylhypoxanthine 5′-monophosphate (Ara-HxMP) showed that the Ara-AMP, in a concentration of 2 or 20%, had a significant effect on the keratitis but that 0.4% Ara-HxMP showed only minimal activity. Ara-AMP was also effective in the treatment of idoxuridine-resistant keratitis. No local toxicity with a high concentration (20%) of Ara-AMP was seen, but the duration of therapy was brief.